Folkestone perennial: the enduring work of art in the re-constitution of place. (October 2016) - Whybrow, Nicolas
Ostensibly contemporary art biennials seek to engage with the places that host them, yet frequently they are viewed critically as elitist 'art world' events that are disconnected from their localities. The aim of this article is to establish how public art works in a given context, both as part of a format prescribed by the art event and in its potential to intersect with the intricate, contingent and varied constellation of the urban location in question. It addresses this central tension by examining the case of Folkestone, a town on the south Kent coast in the United Kingdom that once enjoyed a thriving identity as both seaside resort and gateway to Europe. From the 1960s onwards, a gradual decline set in with the advent of mass global travel, culminating in the deathblow that was dealt by the nearby Eurotunnel's inauguration towards century's end, which signalled the end of the town's ferry link to the continental mainland. A concerted attempt has been underway for a decade now to revitalise the town using the arts, creative industries and education as the drivers of regeneration. One of the main initiatives in this endeavour was the introduction in 2008 of the Folkestone Triennial, a 3-month summer event in which high-profile international artists were commissioned to produce sited artworks for the town, turning it into a form of urban gallery. With successive Triennials occurring in 2011 and 2014, and several works from all three being retained as permanent acquisitions, this article takes stock of the impact of these artistic engagements with the town, showing how, as an ensemble, they interact with one another and asking whether they have the capacity to contribute to a reconstituted identity for Folkestone in an integrated and lasting way.